Pengelolaan Supervisi Pembelajaran Berbasis Kurikulum 2013 di SMK - Riyanto, R. (Universitas Muhammadiyah Surakarta, 2017)
The purposes of this study are: (1) Describing the supervision planning of learningbased on Curriculum 2013 in SMK Pancasila 3 Baturetno Wonogiri Regency. (2)Describing the supervision implementation of learning based on Curriculum 2013in SMK Pancasila 3 Baturetno Wonogiri Regency. (3) Describing the evaluation andfollow-up of supervision of learning based on Curriculum 2013 in SMK Pancasila3 Baturetno Wonogiri Regency. The Type of the research is qualitative research withphenomenological design which conducted in SMK Pancasila 3 Baturetno. Thetechniques data collection with in-depth interviews, observation and documentation.Data analysis using descriptive - qualitative analysis model.The results of the study are : (1) Supervision activity of learning at SMK Pancasila3 Baturetno conducted by good planning. The principal and the vice principal ofcurriculum make a concept of supervision schedule according to applicable scheduleand List Sort Rank (DUK). Then, this concept is coordinated to all teachers as a meansof information about the supervision activity of learning and its schedule. Threeaspects which supervised by principal are instructional administration, learningimplementation and assessment administration. (2) Supervision of learning is doneby observation technique. The principal supervises the class based on the schedule.The assessment is set out in a supervisory instrument and principalâs notebook in theform of scores and descriptions. (3) The evaluation of supervision is conducted afterthe supervised teacher has no teaching duty. The evaluation discusses the resultsof supervision, especially the strength and weaknesses of the supervised teachingin carrying out teaching and learning duties. In general, the results of supervisionsummarized from supervision evaluation activities showing that teachers of SMKPancasila 3 Baturetno are completed in administration, competent in deliveringlessons and completed in assessment administration. However, there are someteachers still having different perceptions in understanding the implementation ofthe Curriculum 2013. Therefore, the principal facilitates to hold MGMP and IHT asa follow-up of supervision.